The monophyly of Magelona F. Müller, 1858 (Polychaeta, Magelonidae): Comments on Meißner et al.’s (2023) reinstatement of Octomagelona Aguirrezabalaga, Ceberio & Fiege, 2001 - Fitzhugh, Kirk; Mortimer, Kate; Brasil, Ana C. Dos Santos (Zootaxa, 2024)
The first published phylogenetic hypotheses involving members of the polychaete taxon Magelonidae Cunningham & Ramage, 1888, were reported by Mortimer et al. (2021), wherein results showed that for the two genera in the family, Magelona F. Müller, 1858, was paraphyletic relative to Octomagelona Aguirrezabalaga, Ceberio & Fiege, 2001. The only option to formally name at least some of the resultant phylogenetic hypotheses was to place Octomagelona into synonymy with Magelona, leaving the definition of Magelonidae redundant with that of a monophyletic Magelona. Meißner et al. (2023) subsequently described specimens as members of new species, Octomagelona borowskii Fiege, Knebelsberger & Meißner, 2023, and O. sp. cf. O. borowskii, with the view that Octomagelona should be maintained as distinct from Magelona. We present reasons why reestablishing the paraphyly of Magelona is scientifically unwarranted.